Effect of Restricted Sight on Right-Turn Driver Behavior with Pedestrians at Signalized Intersection. (14th January 2014) - Jin, Jing; Wang, Wuhong; Wets, Geert; Wang, Xiao; Mao, Yan; Jiang, Xiaobei
Abstract : When the right-turn vehicles share the same phase with pedestrians on divided lanes at intersection, the stopped buses or medium-size vehicles that closed to the right-turn vehicles would block the view of drivers and pedestrians from the far-side of crosswalk. This paper aims at analyzing the changes of lag/gap acceptance behavior with/without considering sight obstruction and the headway of following right-turn vehicles by video observation. Cumulative Weibull distribution function was used to estimate parameters of lag/gap acceptance probabilities. The result showed that right-turn drivers tend to accept a smaller lag/gap with restricted sight, and it would lead to more potential conflicts between right-turn vehicles and pedestrians. However, larger headway of following right-turn vehicles with sight obstruction may result in delay and reduced capacity in right-turn lanes. This study will hopefully improve the understanding of the relationship between visibility and pedestrian-vehicle conflicts.